Keberadaan Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae) Sebagai Vektor Pineapple Mealybug Wilt-associated Virus (PMWaV) Pada Tanaman Nanas - Dewi Sartiami (Jurnal Ilmu Pertanian Indonesia, 2006)
Mealybug can almost be found in all pineapple fields (Ananas comosus (Linnaeus)). The insect is known to be a vector of Pineapple Mealybug wilt-associated Virus (PMWaV). The insect samples taken from pineapple in Bunihayu, Jalancagak, Subang, West Java, were identified in laboratory. Mealybug-ant symbionts were also taken. The ability of this ant to carry the mealybugs from colony reared on kabocha (Cucurbita maxima) to pineapple was also tested at green house level. Only one spesies of mealybug was found on pineapple, i.e. Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae). The mealybugs were found to colonize root, basal of stem and the leaf. Eight ant species were found to be associated with mealybug. There are four species belongs to Pseudolasius genera, two species Cardiocondyla genera, Paratrechina sp. and Dorylus sp. Paratrechina sp. showed the ability to carry D. brevipes from kabocha population to pineapple. Therefore the ants should also be controlled in the total management of PMWav.